Health Care Practitioners’ Determinants of Telerehabilitation Acceptance - Abdullah A. Almojaibel; Niki Munk; Lynda T. Goodfellow; Thomas F. Fisher; Kristine K. Miller; Amber R. Comer; Tamilyn Bakas; Michael D. Justiss (International Journal of Telerehabilitation)
Background: Pulmonary rehabilitation is a multidisciplinary patient-tailored intervention that aims to improve the physical and psychological condition of people with chronic respiratory diseases. Providing pulmonary rehabilitation (PR) services to the growing population of patients is challenging due to shortages in health care practitioners and pulmonary rehabilitation programs. Telerehabilitation has the potential to address this shortage in practitioners and PR programs as well as improve patients’ participation and adherence. This study’s purpose was to identify and evaluate the influences of intention of health care practitioners to use telerehabilitation. Methods: Data were collected through a self-administered Internet-based survey. Results: Surveys were completed by 222 health care practitioners working in pulmonary rehabilitation with 79% having a positive intention to use telerehabilitation. Specifically, perceived usefulness was a significant individual predictor of positive intentions to use telerehabilitation. Conclusion: Perceived usefulness may be an important factor associated with health care providers’ intent to use telerehabilitation for pulmonary rehabilitation.